Lessons from one year experience of pooled procurement of pharmaceuticals: exploration of indicators and assessing pharmacies` performance - Bastani, Peivand (Daru, 2018)
BACKGROUND: Joint procurement of medicines is a way to improve access and justice in developing countries. The aim of this study is to determine local indicators for assessing the performance of joint procurement agencies and compare the indicators in those pharmacies which use centralized purchasing before and after this change. METHODS: This was a mixed method study. In the first qualitative phase, 3 expert panels were held including 20 national experts who were selected through purposeful sampling. Data was analyzed applying a five-stage framework analysis using MAXQDA. In the second quantitative phase, financial, supply and procurement, physical and functional indicators of two hospitals affiliated with joint procurement were assessed and the satisfactions of patients from the pharmacy performance were compared applying a valid questionnaire. Data was analyzed using SPSS through independent test, Paired t-test and ANOVA. RESULTS: Results show that after settlement of joint procurement, the cost of transportation has increased by 54%, a part of the cost of overhead has increased by 30%, the cost of manpower has increased by 88.9% and cost of insurance of warehouses has increased by 71.85% in 2016 compared to 2015. In addition, the total costs of holding were 89.8% of selling revenue. In other words, the profit was about 10% of revenue in total. Moreover the average score of pharmacies under the Holding has been higher than similar ones in all aspects of satisfaction from the patients` points of view. CONCLUSION: The one-year experience of deploying centralized purchasing to supply medicine has led to increased income and patient satisfaction. However, increase in staffing costs, longevity, overhead and warehouse costs have been significant that need appropriate monitoring and interventions. [Figure: see text]